Farmers’ Challenges in Adopting Soil Health Card Recommendations in Saharsa, Bihar (Indian Journal of Extension Education, 2023)
The study was aimed to identify the constraints associated with the adoption of soil health cards recommended by Mandan Bharti Agriculture College (MBAC), Agwanpur in Sattarkataiya block, Saharsa district, Bihar during 2017-2021. Two villages named Barahsher and Puroshottampur Purikh were selected based on the maximum card holders. 100 respondents from each village with Soil Health Card (SHC) were selected. A pretested and well-structured interview schedule was used to collect data, tabulate, and analyze the results. Major constraints faced by farmers were inadequate follow-up by extension agency (71%); soil samples not taken from each farmer’s field (59%), not getting SHC reports in time (57%), and not using of the recommended dose of fertilizers as per SHC recommendation (49%). While major suggestions that came out to tackle the mentioned constraints were that SHC should be issued prior to crop season (70%), Soil sampling laboratory should be established at Block level with highly qualified staff (61%), farmers should be trained to take soil samples (63%). and soil sampling should be based on hands on training of farmers (59%).